Isolation, purification and characterization of inulin and fructooligosaccharides from chicorium intybus and inulinase from aspergillus niger - Mavumengwana, Vuyo Bhongelethu (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2005)
Inulin is a non-digestible carbohydrate fructan polymer consisting mainly of Î² (1â†’2) fructosyl fructose links. Enzymatic hydrolysis of inulin by inulinase results in the production of low D.P (degree of polymerization) oligosaccharides also called fructooligosaccharides(FOS). Isolation of inulin from chicory root (Chicorium intybus) was achieved by first, extraction using deionized water (600C), followed by carbonation (0.1 M Ca(OH)2 and CO2 gas). This was filtered in order to remove the non sugars, thereafter, treated successfully with polyamide 6 powder. A cation exchanger and an anion exchanger were used to further exclude other components such as tannins and pigments. The extracted inulin was quantified using the Somogyi-Nelson colourimetric assay. Chicory root (207 g, 30 % being water) yielded 30 g of the raw extract. A 100 mg of the raw extract was assayed and found to contain 11 % yield of inulin which was 80.2 % in purity and 4 % free fructose. Analysis of the crude and purified inulin extracts on the MALDI TOF spectrometry showed the samples to have a DP of 2 to 22 and 2 to 27 respectively. Maximum inulinase production from Aspergillus niger grown on inulin was observed after 60 hours. The enzyme activity was found to be 1.168 U/ml with a temperature and pH optimum of 30 Â°C and 7.7 respectively. The enzyme proved to be unstable as it progressively lost its total activity during attempts at purification.
Keywords: Aspergillus; Inulin; Chicory -- South Africa